Risk Analysis of Time Delays in The Diara Cileungsi Hotel Construction Project Bogor Regency - Kusuma, Dwi Cahya (International Journal of Engineering, Science and Information Technology, 2021)
The Diara Hotel construction project, which is located in Cileungsi, Bogor Regency, with a building area of approximately 600 m2 and a building height of 24.8 m, has been delayed due to several factors. This study aims to identify risk variables and the highly variable faced by contractors in the risk of time delays in the construction project of Hotel Diara Cileungsi, Bogor Regency. The analysis in this study uses a quantitative descriptive method, which is carried out by surveys, interviews, and distributing questionnaires to respondents. Analysis using software in processing data. The results of the study indicate that there are 34 variables that become risk variables and 7 risk variables with the high ranking risk.